Segmental Versus Total Colectomy for Crohn's Disease in the Biologic Era: Results From The SCOTCH International, Multicentric Study. (12th July 2022) - Pellino, Gianluca; Rottoli, Matteo; Mineccia, Michela; Frontali, Alice; Celentano, Valerio; Colombo, Francesco; Baldi, Caterina; Ardizzone, Sandro; Martí Gallostra, Marc; Espín-Basany, Eloy; Ferrero, Alessandro; Panis, Yves; et al.
Abstract: Background: The extent of resection in colonic Crohn's disease [cCD] is still a topic of debate, depending on the number of locations, the risk of recurrence and permanent stoma, and the role of medical therapy. Methods: The Segmental COlecTomy for CroHn's disease [SCOTCH] international study is a retrospective analysis on six tertiary centre prospective databases, comprising all consecutive, unselected patients operated on between 2000 and 2019 with segmental colectomy [SC] or total colectomy [TC] for cCD. The primary aim was long-term surgical recurrence. Secondary aims were perioperative complications, stoma formation and predictors of recurrence. Results: Among 687 patients, SC was performed in 285 [41.5%] and TC in 402 [58.5%]. Mean age at diagnosis and surgery, disease duration, and follow-up were 30 ± 15.8, 40.4 ± 15.4, 10.4 ± 8.6 and 7.1 ± 5.2 years respectively. Isolated cCD, inflammatory pattern, perianal CD, younger age, longer disease duration and preoperative maximal therapy were more frequent in TC, while SC presented more small bowel locations and perforating disease, required fewer 90-day re-admissions, and fewer temporary and definitive stomas. Morbidity and mortality were similar. The 15-year surgical recurrence was 44% in TC and 27% in SC [ p  = 0.006]. In patients with one to three diseased segments, recurrence risk was related to the omission of biological therapy (hazard ratio [HR] 5.6), the number of segments [HR 2.5], perianal disease [HR 1.9] and paediatric diagnosis [HR 2.8]. Conclusion: When technically feasible, SC is safe and reduces temporary and permanent stoma. Young age, number of locations and perianal disease adversely affect, but postoperative biological therapy significantly reduces, the long-term surgical recurrence.